Mesenchymal Stromal Cell-Based Therapies as Promising Treatments for Muscle Regeneration After Snakebite Envenoming - Sanchez-Castro, E. Eduardo; Pajuelo-Reyes, Cecilia; Tejedo, Rebeca; Soria-Juan, Bárbara; Tapia-Limonchi, Rafael; Andreu, Etelvina; Hitos, Ana B.; Martin, Franz; Cahuana, Gladys M.; Guerra-Duarte, Clara; de Assis, Thamyres C. Silva; Bedoya, Francisco J.; et al. (Frontiers in Immunology, 2021)
Snakebite envenoming is a global neglected disease with an incidence up to 2.7 million new cases every year. Although antivenoms are the so-far the most effective treatment to reverse the acute systemic effects induced by snakebite envenoming, they have a limited therapeutic potential, being unable to completely neutralize the local venom effects. Local damage, such as dermonecrosis and myonecrosis, can lead to permanent sequelae with physical, social, and psychological implications. The strong inflammatory process initiated by snake venoms is associated with poor tissue regeneration, in particular the lack of or reduced skeletal muscle regeneration. Mesenchymal stromal cells-based therapies have shown both anti-inflammatory and pro-regenerative properties. We postulate using allogeneic Mesenchymal Stromal Cells to induce skeletal muscle regeneration in snakebite victims, improving all the three steps of the skeletal muscle regeneration process mainly by anti-inflammatory activity, paracrine effects, neovascularization induction, and microenvironment remodeling. Since snakebite envenoming occurs mainly in areas with poor healthcare, we enlist the principles and potential of MSC therapy and discuss regulatory issues, good manufacturing practices, transportation, storage, and related-procedures that could allow the administration of these therapies, looking forward to a safe and cost-effective treatment for a so far unsolved and neglected health problem.